The Effects of Calina Papaya Leaf Ethanol Extract On Estrus Cycle And Uterus Morphology of Wistar Rats - Haris Setiawan; Sri Wijayanti Wulandari; Fauziana Eka Nurwidyantary; Intan Dewantari (Biosaintifika: Journal of Biology & Biology Education, 2021)
Calina papaya leaf is an Indonesian papaya plant type that has the potential to be used as a medicinal plant. Phytochemical compounds found in papaya leaves act as antifertility agents. The research aimed to study the antifertility effect of Calina papaya leaf ethanol extract on estrus cycle and uterine morphology of wistar rats. The experiment lasted 30 days and involved 25 female wistar rats. The treatment consisted of 5 groups, namely K (distilled water), K+ (contraceptive pill), P1 (Calina papaya leaf ethanol extract 200mg/KgBW), P2 (Calina papaya leaf ethanol extract 300mg/KgBW), and P3 (Calina papaya leaf ethanol extract 400mg/KgBW). The parameters of estrus cycle consisted of estrus cycle phase, total cycle and estrus cycle ratio. Uterus morphological parameters consist of wall thickness of the endometrium, myometrium, and perimetrium. The estrus cycle examination was carried out every day using the vaginal smear method (Giemsa 5%). On the 31st day, surgery was performed and the uterus was taken for histological observation using the paraffin method (HE staining). Data were analyzed using One Way ANOVA with further Duncan’s test. The results showed that a dose of 400 mg/KgBW could affect the estrus cycle with accelerate the estrus phase and increase the estrus cycle ratio compared to the control (P0.05). There was a decrease in endometrium and myometrium wall thickness at a dose of 400 mg/KgBW compared to the control (P0.05). The conclusion of the study is that the ethanol extract of Calina papaya leaves at a dose of 400 mg/KgBW has the potential to be a natural antifertility agent on female wistar rats.